Experimental Study of the Shear Performance of Scrap Tire-Granular Material Composite Columns. (8th May 2020) - Wang, Fengchi; Nie, Xiaomei; Zhao, Hanyu; Hu, Haiming
Abstract : Scrap tires filled with granular materials can be used for geotechnical engineering. However, when subjected to earthquakes and other conditions, shear failure occurs between the tires. In this paper, eight groups of tire-sand composite columns are prepared and tested under shear strength tests. Different vertical forces, sand densities, and loading modes are considered to investigate the shear performance. The failure patterns, load-displacement curves, and stress-strain curves are observed. The results show that the shear failure of composite undergoes three typical stages: overall flexural lateral displacement, transverse compression, and relative interfacial slip. Under monotonic loading, the restriction of the transverse deformation of the composite column is enhanced with increasing vertical force. The overall antidisturbance ability of the composite is enhanced with increasing sand density. The cyclic loading mode can improve the lateral stiffness of the tire-sand composite. The relative motion between the tire-sand interfaces has two forms: elastic creep and interface sliding. Under the hoop effect of the tire, the pores between the particles produce a pseudocohesive force, which causes the shear strength of the tire-sand composite to be higher than that of common sand. A formula is obtained to describe the stress-strain variations in the composite under different vertical forces.